2012
DOI: 10.1371/journal.pone.0035437
|View full text |Cite
|
Sign up to set email alerts
|

Do Dogs (Canis lupus familiaris) Make Counterproductive Choices Because They Are Sensitive to Human Ostensive Cues?

Abstract: Dogs appear to be sensitive to human ostensive communicative cues in a variety of situations, however there is still a measure of controversy as to the way in which these cues influence human-dog interactions. There is evidence for instance that dogs can be led into making evaluation errors in a quantity discrimination task, for example losing their preference for a larger food quantity if a human shows a preference for a smaller one, yet there is, so far, no explanation for this phenomenon. Using a modified v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 40 publications
(50 reference statements)
5
30
2
4
Order By: Relevance
“…If dogs showed this preference on the first test trials, the above chance performance could be achieved without the need for mental representation of the invisible displacement, and there would be no evidence of learning. Marshall-Pescini et al, 2012;Marshall-Pescini, Praoto-Previde, et al, 2011b;Miller et al, 2010;Miller et al, 2009a). The results of these control trials did not reveal any influence of inadvertent cues from the experimenter.…”
Section: Box 51 Controlling For Confounding Variablesmentioning
confidence: 89%
“…If dogs showed this preference on the first test trials, the above chance performance could be achieved without the need for mental representation of the invisible displacement, and there would be no evidence of learning. Marshall-Pescini et al, 2012;Marshall-Pescini, Praoto-Previde, et al, 2011b;Miller et al, 2010;Miller et al, 2009a). The results of these control trials did not reveal any influence of inadvertent cues from the experimenter.…”
Section: Box 51 Controlling For Confounding Variablesmentioning
confidence: 89%
“…No obstante posee la desventaja de que involucra un numeroso compuesto estimular en el cual es imposible distinguir cuales son las señales más salientes que utiliza el perro para discriminar una determinada emoción. En segundo lugar, algunos estudios presentan ciertas claves en forma aislada, ya sea porque en la representación de las personas eliminan una modalidad sensorial, por ejemplo las claves vocales (Marshall-Pescini, Passalacqua, Miletto Petrazzini, Valsecchi, & Prato-Previde, 2012), o porque presentan imágenes o grabaciones en que solo hay un único tipo de información (Nagasawa, Murai, Mogi, & Kikusui, 2011). Si bien estos estudios aportan un mayor nivel de control experimental, muchas veces la dificultad aquí radica en que el perro sea capaz de prestar atención a un estímulo artificial y que la falta de respuesta no pueda atribuirse a una inadecuada codificación sensorial de la información, por ejemplo al presentar señales en dos dimensiones como las fotos.…”
Section: ¿Pueden Los Perros Reconocer Emociones Humanas? Un Análisis unclassified
“…Sin embargo no mostraron en la prueba de elección posterior una preferencia por ninguno de ellos, tal como había ocurrido cuando los perros tenían una experiencia directa con los humanos (Nitzschner, Melis, Kaminski & Tomasello, 2012). Estos últimos resultados contrastan con estudios previos que mostraron que los perros eran capaces de realizar una inferencia de reputación indirecta pero en una situación de "pedir" comida (Kundey et al, 2011;Marshall-Pescini et al, 2012). En el futuro se podrían investigar los factores que limitan la capacidad de los perros en este dominio cuando el reforzador sea social en lugar de comida, por ejemplo, probando, así, este método con otros roles, o con interacciones entre humanos, como ejemplo experimentador-dueño, más que interacciones entre perros y humanos.…”
Section: Estudios Multidimensionalesunclassified
See 1 more Smart Citation
“…In addition, some studies indicate that dogs' performance changes according to the level of familiarity (owner-stranger) with the person present during the task (Elgier et al, 2009;Kerepesi et al, 2014;Marshall-Pescini et al, 2012). For instance, Elgier et al (2009) demonstrated that, in an object-choice task, the extinction of following pointing gestures took longer if the pointer was the dog's owner compared to a stranger.…”
Section: Introductionmentioning
confidence: 99%